Radiação gama na indução de variabilidade em cultivares de arroz irrigado - Silva, Aline Scheer da (2010)
Rice (Oryza sativa L.) has great economic and social importance, especially in southern Brasil, a fact that encourages the search for best cultivars and agronomic characteristics that meet market requirements. Technical support to breeding programs, such as tissue culture, genetic transformation, use of molecular markers or induced mutations, are being increasingly used. The induction of mutations is considered an alternative method to create genetic variability, and the use of ionizing radiation an effective method with which mutants were obtained with characteristics of higher productivity, early maturity, smaller, more resistance to diseases and pests in different species, which are used in breeding programs to develop new cultivars. This study aimed to select mutants with superior agronomic characteristics, which could become new cultivars or serve to backcross in breeding programs for rice. Seeds of BRS Querência and BRS Fronteira were irradiated with 0 (control), 200, 250, 300 and 350 (seed with 13% humidity) and 0 (control), 50, 100, 150 and 200 Gy (seeds with 25% humidity) and then sown in a greenhouse in plastic trays containing soil typical of the rice crop, the moisture was maintained by irrigation manual. Seedlings were evaluated for emergence index and emergence rate and at 14 and 28 days after sowing in height, root length, leaf number and dry weight of shoots and roots. After 28 DAS seedlings were transplanted to the field where complete their life cycle. In the field, were evaluated 36 descriptors morphophysiological used in rice. The results were submitted to analysis of variance and means compared by Tukey's test and regression. Assessments performed in the greenhouse, doses of 300 and 350Gy negatively affected germination and IVE in seeds irradiated with 13% humidity. In seeds with 25% of these variables were reduced to 200 Gy. In the field, in both cultivars, increasing doses of radiation caused reduction in plant size. There were reductions of other descriptors, depending on the cultivar as width and thickness of the grains (BRS Querência) and grains per panicle (BRS Fronteira). The results showed that irradiation affects various parameters on physiology of plants. To determine whether these changes are positive or negative and transmitted by the progeny, need to continue working with the seeds from each M1 plant.